2018
DOI: 10.18203/2320-1770.ijrcog20181339
|View full text |Cite
|
Sign up to set email alerts
|

Genexpert test and endometrial histological findings in infertile women

Abstract: Background: Infertility is a worldwide health problem with very definite physiological, psychological and social implications. According to studies, about 30% of infertility cases are due to the male factors, 40 to 50% have the origin of female factors and 20 to 30% of cases are caused by both male and female factors. Genital tuberculosis is among the main causes of female infertility. Due to its high prevalence, especially in developing countries, work-up of an infertile couple should include evaluation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…were not able to detect any patient positive with Gene Xpert among 81 infertile women suspected of having genital TB as a cause of infertility. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…were not able to detect any patient positive with Gene Xpert among 81 infertile women suspected of having genital TB as a cause of infertility. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…In their study, among the 81 cases who presented with infertility 1 case (1.23%) was found positive for tubercular endometritis and the rest 80 cases (98.7%) had non tubercular findings suggestive of infertility. The study emphasized on sparse number of Mycobacterium tuberculosis in endometrial biopsy due to various reasons such as secondary nature of genital tuberculosis, limitation of infection to the fallopian tube and cyclical shedding of the endometrium making it evident that tuberculosis may not be detected in all cycles 3 . In another study conducted by Saxena et al, among 62 suspected cases of genital tuberculosis GeneXpert showed 1.6% positivity which was less compared to 22.9% positivity on culture.…”
Section: Discussionmentioning
confidence: 99%
“…Fallopian tube in females are most frequently affected (90-100%) followed by endometrium (50-60), ovaries (20-30), cervix (5-15%), vulva and vagina (1%) 2 . Infertility is a worldwide health problem, genital tuberculosis being one of its main causes accounting for nearly 18% infertility cases in India 3 .…”
mentioning
confidence: 99%
“…In both positive cases for TB in CBNAAT, very low MTB was detected. Most previous studies detected TB on endometrial slides, but only a few have diagnosed FGTB on CBNAAT/Xpert [2][3][4]8]. Thangappah found that 6.9% of the endometrial samples were positive [7].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory investigations, such as serology and microscopy, have little value in diagnosis, and culture takes a long time. Polymerase chain reaction (PCR) has high sensitivity but low specificity [ 4 ]. Histopathology of genital/endometrial tissue may detect tuberculosis (TB) by granulomatous lesions; however, it is not diagnostic because granulomas may also be found in other infectious diseases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%